Immunohistochemistry of immune checkpoint markers PD-1 and PD-L1 in prostate cancer. Issue 38 (September 2019) - Sharma, Meenal; Yang, Zhiming; Miyamoto, Hiroshi
Abstract : Abstract: Recent availability of immune checkpoint inhibitors has facilitated research involving programmed cell death protein 1 (PD-1) and its ligand, programmed death-ligand 1 (PD-L1). However, the incidence and clinical implication of PD-1 and PD-L1 expression in prostate cancer remain poorly understood. The current study aimed to determine the status of PD-1/PD-L1 expression in prostate cancer specimens and its prognostic significance. We immunohistochemically stained for PD-1 and PD-L1 in our tissue microarray (TMA) consisting of radical prostatectomy specimens. The expression of PD-1/PD-L1 was designated as positive when moderate to strong staining or weak staining was seen in at least 1% or 10%, respectively, of tumor cells and/or associated immune cells. We then evaluated the relationship between the expression of each protein and clinicopathological features available for our patient cohort. PD-1 and PD-L1 were positive in 3 (1.5%) and 1 (0.5%) of 201 non-neoplastic prostate tissues, and also in 17 (7.7%) and 29 (13.2%) of 220 prostate cancers, respectively. PD-1 and PD-L1 were also expressed in tumor-infiltrating lymphocytes/macrophages in 172 (78.2%) and 33 (15.0%) cases, respectively. PD-L1 expression in tumor cells was more often seen in high pT stage (pT2: 10.8% vs pT3/4: 20.4%; P = .072; pT2/3a: 11.4% vs pT3b/4: 31.6%; P = .013) or lymph node-positive (pN0: 10.1% vs pN1: 27.3%; P = .086) cases, whereas PD-1 expression in tumor cells was not significantly associated with pT/pN stage. In addition, there were no statistically significant associations between PD-1/PD-L1 expression in tumor cells or tumor-infiltrating lymphocytes/macrophages versus patient age, preoperative prostate-specific antigen level, or Gleason score. Kaplan–Meier analysis coupled with log-rank test further revealed no significant associations between PD-1/PD-L1 expression in tumor cells ( P = .619/ P = .315), tumor-infiltrating lymphocytes/macrophages ( P = .954/ P = .155), or either or both of them ( P = .964/ P = .767) versus disease recurrence after radical prostatectomy. PD-1/PD-L1 expression was detected in a subset of prostate cancers. In particular, PD-L1 expression was considerably up-regulated in nonorgan-confined tumors. However, PD-1/PD-L1 expression in our TMA was found to be not very helpful in predicting tumor recurrence in prostate cancer patients who underwent radical prostatectomy.